Adapalene-BPO Reduces Acne Lesions and Scars - Nichols, Emma Hitt (MD Conference Express, 2014)
The current treatment of acne includes topical retinoids, which promote fibroblasts to produce more procollagen. Therefore, it is feasible that topical retinoids may improve preexisting atrophic acne scars or be used for scar prevention. This article discusses a study looking at whether adapalene-BPO treatment could prevent acne scarring and to determine the relationship between primary and secondary acne lesions.